Terapi Urine Dalam Kasus Sakit Gigi Perspektif Fikih - Nurhadi, Ativa; Amin, Abd Rauf Muhammad; Suhufi, Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The world of medicine is experiencing developments in accordance with the times and human abilities. As living creatures, humans in their daily lives will always encounter various types of illnesses, both mild and serious. Alternative medicine is non-medical treatment where the equipment and materials used are not included in standard medical treatment. The type of research used is library research, which is based on qualitative descriptive data. The focus of this research is on the Fiqh Perspective on Urine Therapy in Toothache Cases. Urine therapy used to treat toothache is said to be effective because the internal treatment is gargling. So it is clear that the use of urine as a therapeutic drug is forbidden internally while externally it is permissible considering that the author has found no evidence that can substantiate its prohibition, but it must be cleaned from the body, especially when performing worship.